Enhancement of iron, zinc, and calcium bioaccessibility and bioavailability in green gram (Vigna radiata L.) supplemented with buttermilk through phytate reduction: an in vitro dietary evaluation - Varshanath, Bindhu; Robin, Delvin T.; Meera, Sudha; Dileep, Anusree; Archana, Shylaja; Chandran, Nidhin; Vandana Rani, Madhavan (Frontiers in Nutrition, 2026)
IntroductionPlants supply essential nutrients such as vitamins, minerals, proteins, and dietary fiber, which are required for human nutrition. However, in plant-based diets, specific compounds like phytates can inhibit the absorption of nutrients, leading to potential health problems. Green gram (Vigna radiata L.), a regularly used plant, contains phytic acid at levels ranging from 0.4 to 1.4%. The high levels of phytic acid in green gram can impede the absorption of essential minerals. Systematic alterations to dietary approaches are needed to resolve this issue. Ayurveda mentions the concept of adjuvant (Anupāna) to enhance the availability of nutrients and address any pitfalls in nutrient absorption. This research aims to ascertain if buttermilk (Takra) can serve as a nutritive enhancer in the diet and improve nutrient absorption from green gram.MethodsBioaccessibility of iron, calcium, and zinc in four samples namely- uncooked green gram, cooked green gram, buttermilk and cooked green gram treated with butter milk was assessed using the INFOGEST digestion process. The digested samples were then analyzed by inductively coupled plasma mass spectrometer (ICP-MS) to determine the levels of these micronutrients. Moreover, the bioavailability of these micronutrients is evaluated by treating Caco-2 cells with the final digest and analyzing them using ICP-MS.ResultsThe statistical analysis exhibits that the final digest of cooked green gram treated with buttermilk had considerably higher amounts of bio accessible and bioavailable iron, calcium, and zinc than the untreated sample. Improved bio accessibility and bioavailability were underlined by a significant rise of 68% in iron, 57% in calcium, and 23% in zinc in the buttermilk treated samples.ConclusionThis substantiates Ayurvedic principles by demonstrating that the specific adjuvant, buttermilk increases the bio accessibility and bioavailability of micronutrients such as iron, calcium, and zinc in green gram.